Confidentiality and mental health - Cordess, Christopher (Jessica Kingsley, 2001)
Confidentiality and Mental Health explores the theoretical and practical implications of confidentiality and disclosure for professionals working with people who have mental health problems. The contributors outline the theoretical, ethical, legal and professional issues which underpin decisions about confidentiality. They draw from their practical experience of a range of professional contexts including adolescent forensic psychiatry, criminal law, secure forensic psychiatry, child protection, community psychiatry, psychoanalysis, psychotherapy, social work and nursing. People experiencing mental health problems may need to be able to present and explore deeply disturbing thoughts and actions in a safe therapeutic environment. Professionals may feel caught between individual service users' interests and those of the general public. These tensions can be magnified by the current emphasis on client empowerment and professional accountability, and increased demands for public information and public safety. This comprehensive and topical volume will enable professionals, academics and policy makers to meet both the needs of clients and the demands of society through a responsible and thoughtful understanding of the significance of confidentiality and disclosure.